PERSEPSI MAHASISWA TERHADAP PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN MULTIMEDIA DASAR - Melani , Herdian; Christiani , Yuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of Artificial Intelligence (AI), particularly ChatGPT, has led to its widespread use by students in Basic Multimedia learning, accompanied by differing perceptions regarding its benefits and potential risks to creativity, originality, and the learning process. This study aimed to (1) describe the forms of AI utilization among the 2023 cohort of students in the Art Education Study Program, Faculty of Languages and Arts, Universitas Negeri Padang (FBS UNP), in Basic Multimedia learning; (2) analyze students' perceptions of AI utilization from cognitive, affective, and psychomotor perspectives; and (3) examine the overall tendency of students' perceptions toward AI utilization. This research employed a quantitative descriptive approach. The population consisted of all 98 students from the 2023 cohort of the Art Education Study Program at FBS UNP. Using a total sampling technique, 81 eligible respondents participated in the study. Data were collected through a closed-ended questionnaire using a four-point Likert scale distributed online via Google Forms and analyzed using descriptive statistics based on mean scores. The findings revealed that ChatGPT was the most frequently used AI tool (83.95%), followed by Google Gemini (59.26%) and Canva AI (35.80%). AI was primarily used to generate initial design ideas or concepts (80.25%) and to obtain visual references (53.09%). Students' perceptions of AI utilization were categorized as high across the cognitive (3.21), affective (3.11), and psychomotor (3.08) dimensions, with an overall mean score of 3.13. Furthermore, 83.95% of the students demonstrated high to very high perceptions, indicating that AI is regarded as a valuable learning support tool that facilitates idea exploration, enhances learning effectiveness, and promotes awareness of creativity, originality, academic integrity, and the responsible use of AI.